The effect of crude extract from the black kwao krua mucuna macrocarpa wall.on gonadal structure and function of the nile tilapia Oreochromis niloticus Linn. - Jirarach Srijunngam (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2004